Assessing the Effectiveness of Project-Based Learning in Social Studies Education - Mutawakkil Mutawakkil (Westscience Press, 2024)
Social Studies Education (IPS) plays a crucial role in shaping students' understanding of society, culture, and social issues. In an effort to enhance the effectiveness of IPS education, innovative approaches such as project-based learning have gained significant attention. This literature review aims to evaluate the effectiveness of project-based learning in IPS education. Through the analysis of various related literature, key findings are identified. Project-based learning has been found to improve understanding of IPS concepts, develop critical thinking skills, and increase student motivation to learn. However, challenges such as resource availability and adequate support for educators are also identified. Therefore, recommendations for more effective implementation of project-based learning in IPS education include providing appropriate training for educators and integrating this method holistically into the curriculum. Further research and curriculum development that take these findings into account are expected to enhance the effectiveness of IPS education in the future.